Viniculture in Mendoza from 1990: Between globalization and regional development - Pehuén Barzola-Elizagaray; Anabella Engelman (Íconos)
The objective of this research is to explore the economic characteristics of the productive winegrowing sys-tem in Mendoza (Argentina) in a context of globalization in order to uncover the difference between the local technosphere and ecosphere. In a context of worldwide socioenvironmental crisis it is imperative to conduct an integral analysis of the productive system at all scales that seeks to redesign the technosphere within the current bio-physical limits. In order to accomplish this task, tools that stem from currents of critical environmental thinking, such as ecological economy and environmental history, were employed. The selected methodology is based on the triangulation of qualitative information, using documentary sources and specialized bibliography, with quantitative data from statistical official sources. The results demonstrate a divergent evolution in the past 30 years between this activity and regional development in terms of the pursuit of social wellbeing. The rent accumulation in the commercialization sector and increased possession of land by entrepreneurs is highlighted. In a parallel way, the intensification of the environmental impact and the downturn of the economic and social aspects can be observed as well.